DAMPAK CURAH HUJAN TERHADAP HASIL TANGKAPAN IKAN DI NAGARI KAMBANG BARAT PESISIR SELATAN - Dito Putra Manggala; Dasrizal; Nefilinda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the importance of understanding the effect of rainfall on fish catch yields in Nagari Kambang Barat, Pesisir Selatan Regency. The main research problems include differences in fish catch yields between the rainy and dry seasons, as well as the factors influencing fish catches during periods of high rainfall. The objectives of this study are to determine the effect of rainfall on fish catch yields, to analyze differences in catch yields between the rainy and dry seasons, and to identify the factors affecting fish catch yields in Nagari Kambang Barat, Pesisir Selatan Regency. This research employs a mixed-methods approach. The population consists of all fisherman households (heads of households) in Nagari Kambang Barat, totaling 158 households. A sample of 61 households was selected using proportional random sampling. Data were collected through questionnaires and interviews with relevant stakeholders. The results show that, based on the ANOVA test, the F value obtained was 11.845 with a significance level of 0.041, indicating that rainfall has a statistically significant effect on fish catch yields in Nagari Kambang Barat, Pesisir Selatan Regency. Excessive rainfall negatively affects fishing activities, as prolonged rainfall prevents fishermen from going to sea due, to high waves and strong winds, which pose safety risks. Perception analysis indicates that 73% of fishermen strongly agree that rainfall influences fish catch yields, classified as a “very good” Total Criterion Rate (TCR). Factors influencing fish catch yields include marine environmental conditions, wave and current dynamics, fish feeding patterns and migration, operational difficulties, and limited fishing time. To maintain stable fish catch yields during both the rainy and dry seasons, fishermen are encouraged to observe natural signs such as wind direction, cloud formations, and sea conditions, and to utilize weather information from local radio and village authorities to support safer and more effective fishing decisions.